Research on Basic Performance and Aging Durability of Iron Tailings Asphalt Mixture - Lianping Zhao; Shaoju Hao; Jing Ma (Kuangchan zonghe liyong, 2022)
In order to avoid excessive use of natural sand and gravel materials as aggregates of asphalt mixtures and to comply with the strategic policy of green development, solid waste iron tailings are used to replace sand and gravel materials to prepare a new type of iron tailings asphalt mixture. A mass spectrometer was used to analyze the chemical composition of the selected iron tailings. The penetration, penetration, softening point, ductility, viscosity and aging durability of asphalt mixture under different iron tailings content are studied. The research results show that the optimal preparation temperature of iron tailings asphalt mixture is selected as 180℃. Comprehensive analysis of economic benefits and effectiveness can determine the optimal content of iron tailings is 30%. Compared with the aged iron tailings asphalt material, the penetration and ductility of the two different asphalt mixtures before aging have a tendency to decrease under the same iron tailing content. However, under the effect of the same iron tailings content, the softening point of the two different asphalt mixtures before aging has a tendency to increase. Comprehensive analysis can be obtained: the asphalt mixture prepared with a temperature of 180°C and an iron tailing content of 30% can meet the road requirements of highways. The spectrum change law of all asphalt samples is basically the same. It shows that the structure of modified asphalt mixed with iron tailings is basically the same as that without iron tailings asphalt. However, with the increase of the iron tailings content, the FT-IR spectrum of the asphalt shows a decreasing trend under the same wave number. It shows that iron tailings can effectively improve the physical properties of asphalt.